Livelihood Diversification and Food Security of Youth Headed Households in Coastal Fishing Communities in Ghana - Eshun, E.A. (University of Ghana, 2023)
There is mounting evidence of the significance of gender equality and women's empowerment in obtaining positive livelihood outcomes in fisheries. The contribution of fisheries to GDP of the Ghanaian economy keeps declining due to many factors. Some of these factors are open access nature of the sea, overexploitation, ambiguous policies and climate change. Additionally, the yearly “closed season” have exacerbated the negative effect of reduced income of the youth who depend on fisheries as a source of livelihoods, further impacting their food security. Livelihood diversification is linked to food security which is very important for every household. Communities, households and individuals employ different means to serve as “safety nets” to diversify their income, improve well-being and increase food security. There is however little gendered research on small-scale fisheries and related livelihood enhancement projects. The study assesses the factors that determine the choice of livelihood diversification strategies of youth headed households. It also estimates the impact of livelihood diversification on the food security of these youth headed households. A mixed methods approach was employed to analyze fisheries and livelihood diversification in coastal fishing communities from a gendered perspective. A multistage sampling technique was used to collect primary data from 424 households in 14 coastal communities across the Greater Accra and Central Regions. A probit model was employed to estimate the determinants of livelihood diversification. Except primary education which influence diversification positively, HH characteristics are not significant, implying similar traits of YHH. Ownership of assets are significant and influence diversification positively except TV. Social grouping (group membership) and institutional characteristics (training in current livelihood activities) positively influence diversification. To estimate the food security status, household dietary diversity score (HDDS) and household food insecurity access scale (HFIAS) measure were employed. The inverse probability weighting regression adjustment (IPWRA) estimation procedure is used for the food security estimate. Increased income has a positive correlation to livelihood diversification, which further has a direct correlation to food security for YHH. Results using the content analysis showed a very gendered fisheries supply chain with different roles played by men, women and the youth and their ability to diversify. Men, women and youth experience negative impact of the decline in fisheries on their livelihoods and further their food security status. Skills development programmes targeting YHH to enable effective livelihood diversification should be implemented. Socioeconomic and institutional support systems such as access to education, group membership, etc. to aid YHH to make informed choices about livelihood strategies should be strengthened. Livelihood diversification as a pathway to food security for YHH in coastal fishing communities in Ghana should be encouraged. Finally, livelihood diversification activities must be implemented with a gendered lens in terms of access to the different assets for men and women to achieve equal and greater impact in coastal fishing communities.
PhD. Agribusiness
Keywords: GDP; gender equality; women's empowerment